Tourist events and satisfaction: a product of regional tourism competitiveness - Teixeira, Sérgio (2022)
Purpose – This study aims to analyze the contribution of tourist event and satisfaction with tourism events as a product of regional tourism competitiveness, as well as evaluate factors of competitiveness. Design/methodology/approach – The research followed a quantitative methodology by conducting a questionnaire on the four largest tourist events in Madeira (Carnival, Flower Festival, Atlantic Festival and Wine Festival), an insular island located in Portugal. Findings – The sample consisted of 2,262 tourists surveyed during the year 2017 and structural equation models were used as the statistical method. Results showed that satisfaction is reflected in the client’s loyalty to the choice of a tourist destination and also contributes directly and indirectly to the regional tourist competitiveness. Originality/value – This study contributes to the valorization of local and regional events, perceived by the level of satisfaction and loyalty of tourists, as products of regional competitiveness of a tourist destination.